Implementation of Hashicorp Vault as Multi-Factor Data Communication Security in Integration with Modern Infrastructure - Saragih, Yuliarman; Hadikusuma, Ridwan Satrio; Bijokangko, Resi Sujiwo (Seminar Nasional Teknik Elektro, 2023)
The objective of this research is to examine how HashiCorp Vault can be effectively implemented as a multi-factor data communication security solution alongside modern infrastructure. Safeguarding sensitive data and digital secrets has become crucial in the digital age, particularly in advanced technological environments such as cloud systems, containers, and micro-based settings. The security of data transmission plays a pivotal role in preserving its confidentiality and integrity while being transferred across networks. In this study, HashiCorp Vault has been selected as the solution to enhance the security of the data communication process. By enabling multi-factor authentication and authorization, Vault strengthens security measures by requiring multiple methods of authentication before granting access. Additionally, Vault ensures the protection of digital secrets, including passwords, API keys, and certificates, through encrypted storage, thereby safeguarding them from unauthorized access. Moreover, this research focuses on the integration of Vault with commonly utilized modern infrastructures like Kubernetes, cloud providers, and external authentication systems. This integration enables comprehensive data communication security throughout the entire infrastructure, ensuring the safety and protection of data during its transit across various infrastructure components. To validate the effectiveness of the Vault implementation, a series of tests and performance evaluations will be conducted. These assessments encompass performance measurements, reliability testing of security measures, analysis of potential threats, and identification of relevant mitigations. The outcomes of this research aim to provide insights into the effectiveness and benefits of employing HashiCorp Vault as a multi-factor data communication security mechanism within the context of contemporary infrastructures. Furthermore, the study offers practical guidance to organizations contemplating the use of Vault as a reliable and trustworthy security solution in the everevolving technological landscape.